Asiatic Acid Prevents Retinal Ganglion Cell Apoptosis in a Rat Model of Glaucoma - Huang, Wanjing; Gao, Fengjuan; Hu, Fangyuan; Huang, Jiancheng; Wang, Min; Xu, Ping; Zhang, Rong; Chen, Junyi; Sun, Xinghuai; Zhang, Shenghai; Wu, Jihong (Frontiers in Neuroscience, 2018)
Asiatic acid (AA), a pentacyclic triterpene derived from the tropical medicinal plant Centella asiatica, has been widely used as an antioxidant and anti-inflammatory agent. Evidence regarding the neuroprotective properties of AA is emerging. However, the protective effects of AA and its mechanism in glaucoma are poorly understood. In the current study, we investigate the neuroprotective effect and mechanism of AA on retinal ganglion cells (RGCs) in a rat model of glaucoma. Elevated intraocular pressure (IOP) was induced in adult rats by injecting microspheres into the anterior chamber. AA was intravitreally injected into glaucomatous rats. RGC densities were analyzed by evaluating surviving RGC number of the retinal flatmounts and retinal sections, and the apoptotic cell number were evaluated by analyzing retinal sections. RGC function was assessed by measuring the photopic negative response (PhNR). Retinal Bcl-2, Bax and cleaved caspase-3 expression were determined using a Simple Western System, real-time PCR and immunofluorescence staining. AA reduced the loss of RGCs and decreased the apoptotic RGC number. AA exerted neuroprotective effects and ameliorated retinal dysfunction in impaired RGCs in a rat model of glaucoma. AA protected RGCs by upregulating the expression of the antiapoptotic protein Bcl-2 and downregulating the expression of the pro-apoptotic proteins Bax and caspase-3. This study has provided important evidence indicating that AA may be a potential therapeutic agent for glaucoma.